Job Satisfaction and Job Performance: Systematic Literatur Review Overview SLR - Abdillah Agustya Siwi Nashiroh; Sopiah Sopiah (Jurnal Mutiara Ilmu Akuntansi, 2023)
The purpose of this SLR is to review the relationship between job satisfaction variables and employee performance variables, or job performance, in a company or organization. This SLR research uses the PRISMA method as a data analysis technique. This study examined and reviewed 35 journal articles that were published in the 2019–2023 period, and then researchers filtered topics and sub-topics using the Emerald database. ScienceDirect, Google Scholar, and Taylor & Francis From this database, 50 eligible journal articles were obtained, then filtered again, and the results were 35 eligible journal articles, which the researchers included in this systematic literature review journal article. The results of this analysis show that almost 35 journal articles state that job satisfaction will influence employee performance, which is influenced by several other factors, such as work environment, work motivation, and commitment.